The relationship between implicit absenteeism and grit and compassion fatigue in female neonatal nurses - Chen, Xushu; Li, Xiaowen; Hou, Shulin; Yang, Ru; Shi, Zeyao (Frontiers in Public Health, 2025)
IntroductionImplicit absenteeism is a growing concern among nurses, as it may reduce nursing productivity and affect the quality of nursing services and patients’ health. This study aimed to investigate the status and influencing factors of implicit absenteeism among female nurses in neonatal units and to explore the correlations between compassion fatigue, grit, and implicit absenteeism.MethodAn anonymous online questionnaire was administered to female nurses in a neonatal unit from August to October 2024 using the General Information Questionnaire, Stanford Implicit Absenteeism Scale, Compassion Fatigue Short Scale, and self-reported short Grit Scale (Grit-S).ResultsIn total, 269 female neonatal unit nurses were included in our study. The implicit absenteeism score of female neonatal nurses was (14.41 ± 4.08). Age, education, and years of work experience were the main factors influencing implicit absenteeism among female nurses in the neonatal unit (all p < 0.05). In addition, implicit absenteeism was positively correlated with compassion fatigue (r = 0.672, p < 0.01) and grit (r = 0.420, p < 0.01). Additionally, compassion fatigue was positively correlated with grit (r = 0.559, p < 0.01).ConclusionFemale nurses in neonatal units have high rates of implicit absenteeism. Clinical managers should pay particular attention to the implicit absenteeism and physical and mental health of female nurses with bachelor’s degrees or above, those over 30 years of age, and those with more than 10 years of work experience. Simultaneously, governments and healthcare organizations need to develop interventions to promote the physical and mental health of nurses, reduce implicit absenteeism, and further contribute to the stable development of the nursing workforce.